Ionospheric Turbulence: A Challenge for GPS Loss of Lock Understanding. Issue 7 (27th July 2022) - De Michelis, P.; Consolini, G.; Pignalberi, A.; Lovati, G.; Pezzopane, M.; Tozzi, R.; Giannattasio, F.; Coco, I.; Marcucci, M. F.
Abstract: Ionospheric irregularities may affect electromagnetic signals propagating through the ionosphere and consequently contribute to the malfunctioning of the Global Navigation Satellite Systems hindering their accuracy and reliability. In this study, we use data recorded on board two of the three satellites of the Swarm constellation (namely, Swarm A and Swarm B) from 15 July 2014 to 31 December 2021 to assess the possible dependence of the Global Positioning System (GPS) signals loss of lock on the presence of a specific kind of ionospheric irregularities. To accomplish this task we study the scaling features of the electron density fluctuations through the structure function analysis simultaneously to the occurrence of loss of lock events through measurements recorded by the Langmuir probes and the precise orbit determination antennas on board Swarm A and Swarm B satellites. We find that the plasma density irregularities in a turbulent state characterized by intermittent structures and extremely high values of the Rate Of change of electron Density Index can lead to GPS loss of lock events. This is always true at mid and high latitudes, especially inside the auroral oval. In the equatorial belt, this happens in at least 75% of identified GPS loss of lock events that basically coincide with the occurrence of plasma bubbles. Plain Language Summary: One of the natural factors that most contributes to the malfunctioning of Global Navigation Satellite Systems and leads to a degradation of their performance, accuracy and reliability, is represented by ionospheric irregularities. In this work, using data recorded by the European Space Agency Swarm constellation mission, we show for the first time that turbulence and extremely high values of the Rate Of change of electron Density Index are at the base of those ionospheric irregularities responsible for Global Positioning System loss of lock events. This result represents an important step forward in the perspective of developing a prediction model of such events, which could be significant in the framework of Space Weather purposes. Key Points: Global Positioning System (GPS) loss of lock events are discussed according to the dynamical status of the ionosphere Ionospheric irregularities at the base of the GPS loss of lock events present an intermittent turbulent nature Extremely high values of Rate Of change of electron Density Index are associated with GPS loss of lock events